Pemanfaatan Printed Circuit Board (Pcb) Motherboard Bekas Untuk Pembangkit Listrik Portabel - Pebriansyah Putra; Yusnimar Sahan; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Galvani cells which are cells based on chemical reactions that can produce electric current. In this research, the generator cell was built to produce electricity. Galvani cells is consisting of zinc and used as a anodes, the motherboard printed circuit board (PCB) is used as a cathode, and a solution of NaCl as an electrolyte. The aim of this research is to estimate the performance of the galvani cell using the types of electrolyte solutions NaCl and NaOH with variation concentrations (9%, 12%, and 15%) and electrode surface area (5 cm x 10 cm, 6 cm x 10 cm, 7 cm x 10 cm). Cell performance is measured by multitester equipment and LED lights (8 volt). The results shown that the generator cell can produce electric power of 6.82 volts optimally by using 15% NaOH and 7 cm x 10 cm electrode surface area applied for this research.Keywords: electrode, electrical voltage, PCB motherboard, zinc.